Integrated treatment of the severely injured patient with coexistent comorbidities. A case report and literature review - Pedrazzini, Alessio; Martelli, Alessandra; Magotti, Maria Grazia; Degli Antoni, Anna Maria; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2015)
Major trauma represents a paradigmatic clinical condition, needing multidisciplinary and structured approach. When a patient is affected by significant comorbidities such as diabetes mellitus and other conditions that compromise the immune competence the risk of infections in the presence of exposed fractures is remarkably high. Although usually managed by multidisciplinary teams, these patients often have unfavorable functional outcomes. We describe here the case of a young diabetic and immunosuppressed man, treated for a destroying injury of the left lower limb, with more than 60 centimeters of multiple fractures exposition. The prompt and fast integration of several different competences led to favorable functional outcome, without any severe local or systemic complication. Therefore, in severely injured patients, especially when affected by significant comorbidities, a quick and highly integrated treatment, provided by a polyspecialistic team, is crucial for reducing unfavorable outcomes and improving the recovery rate.